2001
DOI: 10.1258/0004563011900731
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in haemodialysis: immediate changes caused by passage of blood through the dialyser

Abstract: Oxygen free radicals have been implicated in the long-term complications of maintenance haemodialysis. Studies that have probed into the mechanisms of oxygen radical production have implicated the bio-incompatibility of dialysis membranes. Changes between the arterial (inlet) and venous (outlet) points of a dialyser may give a better picture of blood±membrane interaction. There are very few studies on changes across the dialyser. Hence, it was planned to study the immediate changes that occur due to passage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…This time is quite short for the correction of reducing system by HD, which was damaged by uremia, and there remains a possibility that these decreases are brought about by absorption to the dialyzer membranes or the surface of dialysis circuits. One group reported both pro- and anti-oxidative changes occurring immediately and caused by the passage of blood through the dialyzer though the underlying mechanism was still unclear [8, 9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time is quite short for the correction of reducing system by HD, which was damaged by uremia, and there remains a possibility that these decreases are brought about by absorption to the dialyzer membranes or the surface of dialysis circuits. One group reported both pro- and anti-oxidative changes occurring immediately and caused by the passage of blood through the dialyzer though the underlying mechanism was still unclear [8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…In the nephrological fields, many studies employ LOOH to evaluate oxidative stress in end-stage renal failure, uremia and hemodialysis (HD). Most of these studies identified an increase of LOOH because of increased oxidative stress [2,6,7,8,9,10]. LOOH is commonly treated as the end-product of an oxidative reaction intermediated by reactive oxygen species (ROS) or reactive nitrogen species.…”
Section: Introductionmentioning
confidence: 99%
“…[132324] Reuse of membranes is said to be associated with less complement activation than fresh membranes as a result of fixation of plasma proteins to the membranes and hence lead to less ROS production. [12] We found an increase in MDA as a result of reuse of the membrane ( P <0.05).…”
Section: Discussionmentioning
confidence: 80%
“…[89] Even a single session of hemodialysis increases lipid peroxides and decreases antioxidants. [10–12] However, there are only a few reports on effect of reuse of the dialyzer membrane on oxidative stress. [1314] Most of the studies with the reuse of dialyzer are experimental studies probing into the reactive oxygen species production as an index of the polymorphonuclear leukocyte (PMNL) function[15] and the complement activation[16] as a result of reuse of the dialyzer rather than difference in the oxidative stress situation between fresh and reuse dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…17,31,32 In addition, HD membrane materials may activate neutrophils 33 and platelets. 34 The abrupt change of hemodynamic and metabolic balance caused by dialysis may also add to the development of OS.…”
Section: Discussionmentioning
confidence: 99%